2013
DOI: 10.1177/0957926513508856
|View full text |Cite
|
Sign up to set email alerts
|

‘Maybe it is prejudice … but it is NOT racism’: Negotiating racism in discussion forums about Gypsies

Abstract: This article addresses the ways in which opposition towards Gypsies is debated, with particular regard to whether or not this opposition constitutes racism or prejudice towards a group shown to be vulnerable and subject to discrimination. A discursive analysis of a corpus of internet discussion forums about Gypsies in the UK is undertaken. The analysis demonstrates that opposition towards Gypsies can be presented as racist; however, such accusations are met with criticism so that writers become accountable for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 26 publications
3
64
0
1
Order By: Relevance
“…Goodman and Rowe () investigated the use of these terms further after noticing people distinguishing the meanings of these words. In online discussion forums about Gypsies, they found that alongside many people orienting to the cultural taboo against prejudice, others acknowledged that a position may be prejudiced but that it is not racist.…”
Section: Challenging Our Understanding Of ‘Prejudice’mentioning
confidence: 99%
“…Goodman and Rowe () investigated the use of these terms further after noticing people distinguishing the meanings of these words. In online discussion forums about Gypsies, they found that alongside many people orienting to the cultural taboo against prejudice, others acknowledged that a position may be prejudiced but that it is not racist.…”
Section: Challenging Our Understanding Of ‘Prejudice’mentioning
confidence: 99%
“…The Internet has provided new ways for us to conduct interviews and focus groups (Jowett, Peel & Shaw 2011;Stewart & Williams 2005) as well as offering a wealth of unsolicited data in the form of websites, blogs, and online discussion forums. In particular there is a growing body of discourse analytic and, more broadly, critical research that examines online interaction in the form of online discussion boards (e.g., Bennett & Gough 2013;Callaghan & Lazard 2012;Goodman & Rowe 2014;Horne & Wiggins 2009;Lamerichs & te Molder 2003;Sneijder & te Molder 2004;Veen et al 2010). Although it is important to note that discourse analysis is not automatically a critical endeavour (Gough, McFadden & McDonald 2013), discursive approaches are commonly employed by critical psychologists.…”
Section: Introductionmentioning
confidence: 98%
“…However, the resulting content of these sites can nonetheless be examined for the ways in which "coded language" can be employed to convey covert racialized meanings while avoiding the type of moderation practices applied to overtly racist posts (Hughey & Daniels, 2013), thus offering extensions of the research on more subtle forms of racism discussed above. In addition, some studies have provided evidence that even on some non-moderated sites participants may produce racist discourse in more restrained ways than had previously been documented (e.g., Daniels, 2009b;Malmqvist, 2015), and that participants may deny or contest racism in similar ways to those documented by the research based on offline settings described above (e.g., Goodman & Rowe, 2014).…”
Section: Online Texts and Interactionsmentioning
confidence: 81%